Gyrotron anode voltage control in EAST ECRH system - Xu Weiye; Xu Handong; Zhang Jian; Guo Fei; Sun Haozhang (EPJ Web of Conferences, 2023)
Four diode-type gyrotrons are used in the EAST ECRH system now. The anode is one of the main components of the gyrotron. We can control the output power of the gyrotron by changing the anode voltage. An anode voltage control system for ASIPP anode power supplies was developed based on the ethernet CompactDAQ chassis NI-cDAQ-9185. The anode voltage can be controlled up to 30 kV, and the maximum current is 100 mA. The maximum modulation frequency is 5 kHz at a 50% duty cycle.